Assesment of Rifle Criteria in Acute Renal Failure in Hospitalised Patients - and Vikram Prabha3, Ritesh Vernekar1,2, (Recent Research in Science and Technology, 2011)
Acute renal failure (ARF) is a common complication of critical illness, which is associated with high mortality and has a separate independent effect on the risk of death. ARF is common in the intensive care unit (ICU). The high prevalence of ARF in the ICU setting necessitates a Ã¯Â¬Ârm understanding by critical care providers of the salient issues related to timing of initiation of renal replacement therapy (RRT), choice of modality, and optimal dose, all of which remain subjects of substantial debate and active clinical investigation. We report our series of progression between stages of RIFLE classification and to relate the classification to need for renal replacement therapy, mortality/morbidity in critically ill patients.